Effect of ceramic translucency and luting cement shade on the color masking ability of laminate veneers - Bassem S. M. Kandil; Amena M Hamdy; Ahmed K Aboelfadl; Mohamed I El-Anwar (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study was to evaluate the effect of ceramic material types, degree of veneer translucency, and luting cement shades on masking the underlying dark dental substrate to achieve best esthetics. Materials and Methods: In this in vitro study, 56 specimens each of 0.5-mm thickness were fabricated from two esthetic veneer materials Vita Enamic and Vita Suprinity, with two different translucencies, i.e., HT and T. To simulate the color of a dark underlying dental structure, background discs with C3 shade were fabricated using resin composite. The ceramic specimens with varying translucencies were cemented on the dark background of the resin composite with A1 and opaque white shades of resin luting cement. Color difference (ΔE) values from a reference color (A1 shade) were calculated using a spectrophotometer. The results were then statistically analyzed using three-way ANOVA test (α = 0.05). Results: The ΔE values of both ceramic systems were affected by both the degree of veneer translucency (P = 0.00) and the luting agent shade (P = 0.016). The use of an opaque luting agent and T translucency resulted in a decrease in the ΔE* values for all ceramics tested, regardless to the material type. Suprinity and Enamic showed similarity in the masking ability of dark substrate after cementation. Conclusion: None of the 0.5-mm veneers of the two ceramic systems could reach A1 shade without a detectable color difference after cementation. The change in degree of veneer translucency was more effective than the change in luting agent shade in masking the underlying dark substrate.